2017
DOI: 10.1186/s41182-017-0046-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of tungiasis with a two-component dimeticone: a comparison between moistening the whole foot and directly targeting the embedded sand fleas

Abstract: BackgroundTungiasis (sand flea disease) is caused by the penetration of female sand fleas (Tunga penetrans, Siphonaptera) into the skin. It belongs to the neglected tropical diseases and is prevalent in South America, the Caribbean and sub-Saharan Africa. Tungiasis predominantly affects marginalized populations and resource-poor communities in both urban and rural areas. In the endemic areas, patients do not have access to an effective and safe treatment. A proof-of-principle study in rural Kenya has shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
3
32
0
Order By: Relevance
“…Targeting school-aged children in school for diagnosis and treatment of tungiasis, using recently evaluated safe and effective treatment options, namely dimeticone or neem oil [2, 28, 29], might be the most cost-effective way to reduce the disease burden given that the affected resource-poor communities do not have access to optimal medical care and limited ability to pay for expensive medications. However, the treatment must be provided every time a new infection in a child is detected by the teachers to prevent the life cycle being introduced into classrooms with a cracked or natural sand/mud floor, and to break the cycle at home.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting school-aged children in school for diagnosis and treatment of tungiasis, using recently evaluated safe and effective treatment options, namely dimeticone or neem oil [2, 28, 29], might be the most cost-effective way to reduce the disease burden given that the affected resource-poor communities do not have access to optimal medical care and limited ability to pay for expensive medications. However, the treatment must be provided every time a new infection in a child is detected by the teachers to prevent the life cycle being introduced into classrooms with a cracked or natural sand/mud floor, and to break the cycle at home.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomised controlled trials have shown that embedded sand fleas can be effectively killed by the application of a synthetic oil containing two different dimethicones [ 44 , 45 ]. The efficacy varied between 78% and 95%.…”
Section: Treatmentmentioning
confidence: 99%
“…Its mode of action is purely physical. The topical application of this product has been proved highly effective in randomized control trials in Kenya and Uganda in patients with up to 30 embedded sand fleas [29, 48]. Here we show that the formula is also effective in patients with several hundred of embedded sand fleas located in clusters and in several layers on top of each other in hyperkeratotic or partially necrotizing skin.…”
Section: Discussionmentioning
confidence: 59%
“…Here we show that the formula is also effective in patients with several hundred of embedded sand fleas located in clusters and in several layers on top of each other in hyperkeratotic or partially necrotizing skin. While in simple tungiasis an application of a few drops of the dimeticone—targeted to the abdominal cone which protrudes through the skin–are sufficient [48], in very severe tungiasis the skin needs to be intensively wetted and treatment should be repeated after 24 hours.…”
Section: Discussionmentioning
confidence: 99%